1976
DOI: 10.2134/agronj1976.00021962006800010006x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Response in Corn as Influenced by Genetic Variability1

Abstract: Influence of genetic variability on Zn response in recently improved corn (Zea mays L.) genotypes has not been investigated. Therefore, eight genotypes representing indigenous, hybrid, and composite varieties, were evaluated in the greenhouse using a Zn deficient loamy sand soil (Typic Torripsamments) at 0 (original soil), 5, and 10 ppm Zn applied to the soil. Zinc deficiency symptoms, dry matter yield response (6 weeks after sowing), Zn concentration, and P/Zn and Fe/Zn ratios were the criteria for evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 3 publications
1
7
0
1
Order By: Relevance
“…Phytosiderophores released from Fe-deficient (33,34) or Zn-deficient roots (36) possess a high capacity to enhance solubility and mobility of Zn by chelation from sparingly soluble Zn compounds in calcareous soils. As indicated by the present results, the different susceptibility to Zn deficiency of genotypes within a graminaceous species such as in wheat (8,9,28), maize (5,30), sorghum (29), rice (7), and oat (4) may be related to different capacities of genotypes to release Zn-mobilizing phytosiderophores from roots. In the case of Fe deficiency, the rate of phytosiderophore release by various graminaceous species (13,23) or cultivars within a graminaceous species (6,10) is positively correlated with their chlorosis resistance on calcareous soils.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Phytosiderophores released from Fe-deficient (33,34) or Zn-deficient roots (36) possess a high capacity to enhance solubility and mobility of Zn by chelation from sparingly soluble Zn compounds in calcareous soils. As indicated by the present results, the different susceptibility to Zn deficiency of genotypes within a graminaceous species such as in wheat (8,9,28), maize (5,30), sorghum (29), rice (7), and oat (4) may be related to different capacities of genotypes to release Zn-mobilizing phytosiderophores from roots. In the case of Fe deficiency, the rate of phytosiderophore release by various graminaceous species (13,23) or cultivars within a graminaceous species (6,10) is positively correlated with their chlorosis resistance on calcareous soils.…”
Section: Discussionmentioning
confidence: 54%
“…Alternatively, the selection and breeding of plant genotypes with higher efficiency in acquisition of Zn from soils is a realistic approach. The existence of such genotypes within a given species is well known as shown for maize (5,30), navy beans (3), soybean (22), grapevine (17), and wheat (8,28).…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the Zn response among cultivars of various crops has been reported by several workers (Ambler and Brown, 1969;Safaya and Singh, 1977;Shukla and Ra], 1974, 1976, 1980Shukla et al 1973). This variability has been attributed to the differential capacity of cultivars to exploit soil Zn and translocate it to the metabolically active parts of the plant.…”
Section: Introductionmentioning
confidence: 86%
“…Pavliková et al (1997) confirmed the positive effect of humate on the decrease of Zn content in barley and oats but in maize and poppy Zn content increased. Moreover, maize genotypes (inbred lines, hybrids) differ in their zinc requirements as well as in the uptake and translocation ability (Shukla and Ray 1976). Also, the maize inbred lines property of high or low zinc concentrations could be inherited in hybrids.…”
mentioning
confidence: 99%